Synergy and innovation of digital business solutions and “smart city” infrastructure - P. A. Levchaev (Цифровая трансформация)
Currently, there is a rapid development of digital technologies that determine not only innovative trends in the development of economic entities, but also cause possible synergistic changes in the future. Digitalization of all spheres of the modern socio-economic system leads to the active introduction of innovative developments in our daily lives, but also determines the possible risks. The article uncovers the controversial issues of the digital economy, pays attention to the current state of digital technologies, economic principles and provisions of the formation and features, characteristics of the digital services economy, its capabilities, as well as makes forecasts of the development of digitalization processes in society.